Pau rosa (Aniba rosaeodora): An extractivist potential - Farias, Lucas Eduardo Lopes; Monteiro, Breno Jorge Zeferino; Ferreira, Joseph Pina Bonfim; Cunha, Breno Porto de Oliveira; Serra, Ana Vitória Pinheiro; Silva, João Paulo Amaral da; Costa, Luana Cristhiny Silva da; Oliveira, Eberth Gonçalves Rocha de; Silva, Rogério Tavares da; Baía, Diana Brandão; Souza, Gertrudes Namias Tocantins de; Albuquerque, Vivian Carolina Nascimento de (Seven Editora, 2023)
Pau-Rosa (Aniba rosaeodora), which belongs to the lauraceae family, is a species with high added economic value. Its value is based on the extraction of its essential oil, which is highly prized by the chemical, cosmetic and food industries. Its exploitation began in 1882 in French Guiana, when the extraction of its oil generated interest in the perfumery industry because it has a sweet, woody smell. The great interest shown by the industries in the essential oil has motivated producers to plant the species. However, there is a limited supply of seedlings for sale, as its exploitation was unsustainable, so most of the trees were felled to produce the oil in distillation plants. Essential oils are complex mixtures of volatile substances that dissolve in fat, propagate an aroma, are liquid and are normally obtained by hydrodistillation and steam distillation, where steam distillation is the most widely used in industry. During the essential oil extraction process, the water that drags the volatile constituents becomes aromatized, which is called hydrolate. DOI:https://doi.org/10.56238/uniknowindevolp-143